Sepsis, Septic Shock, and Fatal Exertional Heat Stroke. Issue 1 (January 2015) - Epstein, Yoram; Roberts, William O.; Golan, Ron; Heled, Yuval; Sorkine, Patrick; Halpern, Pinchas
<x xml:space="preserve">Abstract</x> Exertional heat stroke (EHS) is a clinical syndrome of hyperthermia, encephalopathy, and multiorgan dysfunction that can be irreversible and fatal. While prompt recognition and immediate, aggressive total body cooling can prevent progression of the clinical syndrome, even a short delay can exacerbate the effects of hyperthermia-induced changes. EHS is linked to an inflammatory response that is akin to the systemic inflammatory response syndrome (SIRS). However because EHS is not a common problem in most hospital intensive care units and is not in the usual list of SIRS causes, it may be overlooked easily. Furthermore normalizing the body temperature of patients with EHS, especially when hyperthermia recognition and total body cooling are delayed, may not prevent SIRS and its clinical consequences. This narrative review focuses on the inflammatory response behind the pathway leading to EHS-associated organ pathology and recommends a new insight to possible clinical interventions beyond whole body cooling.